BIOETHICS AT THE INTERSECTION OF A COMPLEX NEW REALITY - ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
Bioethics is a broadly interdisciplinary field of inquiry concerning the application of the biomedical sciences to health and life, at the intersection of several disciplines, such as medicine, biology, ethics, philosophy, theology and law. But even sociology, psychology, or psychoanalysis are also involved. In 1970, the American oncologist Van Rensselaer Potter, in the article entitled Bioethics, the science of survival, resumed a year later, in his book, Bioethics: bridge to the future, ascertained an extraordinary development of the scientific knowledge, especially those of biology, on the one hand, and on the other, a delay of the theoretical thinking necessary for the use of these ones, thus proposing a new science – the science of survival – based on the alliance between biological knowledge („bio”) and the one of the human values („ethics”). The domain of bioethics, according to Potter, had to include all the relative dimensions to the survival of the human species and the planet, like: the control of the population, peace, poverty, ecology, animal life, the welfare of the humanity, etc.